Functions of the UL51 protein during the herpesvirus life cycle - Liu, Xiaolan; Wang, Mingshu; Cheng, Anchun; Yang, Qiao; Tian, Bin; Ou, Xumin; Sun, Di; He, Yu; Wu, Zhen; Zhao, Xinxin; Wu, Ying; Zhang, Shaqiu; et al. (Frontiers in Microbiology, 2024)
The herpesvirus UL51 protein is a multifunctional tegument protein involved in the regulation of multiple aspects of the viral life cycle. This article reviews the biological characteristics of the UL51 protein and its functions in herpesviruses, including participating in the maintenance of the viral assembly complex (cVAC) during viral assembly, affecting the production of mature viral particles and promoting primary and secondary envelopment, as well as its positive impact on viral cell-to-cell spread (CCS) through interactions with multiple viral proteins and its key role in the proliferation and pathogenicity of the virus in the later stage of infection. This paper discusses how the UL51 protein participates in the life cycle of herpesviruses and provides new ideas for further research on UL51 protein function.